Nucleolar Proteins Suppress Caenorhabditis elegans Innate Immunity by Inhibiting p53/CEP-1 - Fuhrman, Laura E. (Public Library of Science, 2009)
The tumor suppressor p53 has been implicated in multiple functions that play key roles in health and disease, including ribosome biogenesis, control of aging, and cell cycle regulation. A genetic screen for negative regulators of innate immunity in Caenorhabditis elegans led to the identification of a mutation in NOL-6, a nucleolar RNA-associated protein (NRAP), which is involved in ribosome biogenesis and conserved across eukaryotic organisms. Mutation or silencing of NOL-6 and other nucleolar proteins results in an enhanced resistance to bacterial infections. A full-genome microarray analysis on animals with altered immune function due to mutation in nol-6 shows increased transcriptional levels of genes regulated by a p53 homologue, CEP-1. Further studies indicate that the activation of innate immunity by inhibition of nucleolar proteins requires p53/CEP-1 and its transcriptional target SYM-1. Since nucleoli and p53/CEP-1 are conserved, our results reveal an ancient immune mechanism by which the nucleolus may regulate immune responses against bacterial pathogens.